ANALISIS KINERJA SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENATAAN PEDAGANG KREATIF LAPANGAN (PKL) DI KOTA PALANGKA RAYA (Studi Pedagang Kreatif Lapangan di Jalan Yos Sudarso Kota Palangka Raya) - Rivaldo, Ferdy; Mujiarti Ulfah, Sri; Suprayitno (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
The purpose of this study was to determine how the performance of the Civil Service Police Unit in the arrangement of creative field traders in Palangka Raya City. To find out what are the factors that affect the performance of the Civil Service Police Unit in structuring creative field traders in Palangka Raya City. The theory used in this study is the theory of organizational performance according to Dwiyanto (2008:50), namely productivity, service quality, responsiveness, responsibility, and accountability. The research method used is qualitative research. After the data is collected, it is reduced and presented, and after that a temporary conclusion is drawn about the data relating to the problems being researched and analyzed after that only the final conclusion is drawn. The performance of the Civil Service Police Unit in the Arrangement of Creative Field Traders in Palangka Raya City has been well implemented, it can be seen from the productivity, service quality, responsiveness, responsibility, and accountability. Human resources, infrastructure, and budget are factors that affect the performance of the Civil Service Police Unit in the Arrangement of Creative Field Traders in Palangka Raya City.